Hypoglycaemia as predictor of cardiovascular accidents - E. V Doskina; B. M Tankhilevich (КардиоСоматика, 2013)
Diabetes mellitus type 2 is not only a chronic disease, but also refers to a group of constantly progressing pathologies. Regardless of the level of development of medicine and used therapeutic approaches, mortality from cardio-vascular complications of diabetes exceeds the figures of the General population. According to the results of Veterans Affairs Diabetes Trial it was revealed that severe hypoglycemia are predictors for the development of myocardial infarction and acute disturbance of cerebral blood circulation. Pledge of successful treatment of patients with type 2 diabetes is the adequate choice of target values of glycemia and maintaining it by means of a combination of curative (observance of dietary recommendations, reception of hypoglycemic drugs, etc.) and not drug-induced (by which primarily active self-monitoring of blood glucose) activities.